7d-2=4d+13

Simple and best practice solution for 7d-2=4d+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7d-2=4d+13 equation:


Simplifying
7d + -2 = 4d + 13

Reorder the terms:
-2 + 7d = 4d + 13

Reorder the terms:
-2 + 7d = 13 + 4d

Solving
-2 + 7d = 13 + 4d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-4d' to each side of the equation.
-2 + 7d + -4d = 13 + 4d + -4d

Combine like terms: 7d + -4d = 3d
-2 + 3d = 13 + 4d + -4d

Combine like terms: 4d + -4d = 0
-2 + 3d = 13 + 0
-2 + 3d = 13

Add '2' to each side of the equation.
-2 + 2 + 3d = 13 + 2

Combine like terms: -2 + 2 = 0
0 + 3d = 13 + 2
3d = 13 + 2

Combine like terms: 13 + 2 = 15
3d = 15

Divide each side by '3'.
d = 5

Simplifying
d = 5

See similar equations:

| x/4+3=x | | x^2+4x=4x+32 | | 5x+10=2(2x+6) | | 13-8x=143-43x | | -4(4y-8)-y=-2(y-4) | | 3y-12x=15 | | -3(y+3)=2y+21 | | h=5vt+19t^2 | | 4x^2-17x+22=4x+2 | | 3x+8=52-9x | | 8-(4-12t)+2=3t+2(7-3t) | | 3g+4(-8+3g)=1-g | | -5v-31=3(v-5) | | 6+2(3j-2)=4(l+j) | | 8=n*18 | | -8w+6(w-2)=-4 | | 3(x-6)+2x=5(x+2)-28 | | 10-10x=70-24x | | 4(x-20)=24x | | -16+x=10x | | 4(x-20)=24 | | 6p-9=-5p-42 | | 29-3x=-53 | | 30a^6-104a^5=-90a^4 | | 6p-9=5p+42 | | 5x-5y=3 | | a-2(a-16)=7a | | 5x+2=4x-5 | | 7x+18x=75 | | -5.9-3x=-2.6 | | 3(x+2)-2=5(x+1)-2x | | a-18=14 |

Equations solver categories